2014
DOI: 10.5152/tjar.2014.35693
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Flurbiprofen on Postoperative Sore Throat and Hoarseness After LMA-ProSeal Insertion: A Randomised, Clinical Trial

Abstract: Objective: We hypothesized that flurbiprofen lozenges reduce the ProSeal laryngeal mask airway (LMA) related symptoms of Post Operative Sore Throat (POST), hoarseness and dysphagia compared to placebo lozenges.Methods: Eighty American Society of Anesthesiologists (ASA) I-II patients undergoing general anaesthesia with LMA were included in this prospective, randomized, placebo-controlled clinical and single centre (university hospital) study. Group F received an 8.75 mg flurbiprofen lozenge (Strefen ® ) and Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
(16 reference statements)
0
11
1
1
Order By: Relevance
“…The pre‐operative administration of a flurbiprofen lozenge reduced the severity, although not the incidence, of early postoperative sore throat . A pre‐operative 2 mg.kg −1 tramadol gargle reduced both the incidence and severity of sore throat for up to 24 h postoperatively in a small study of 50 patients , although 100 mg of intravenous hydrocortisone had no effect .…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…The pre‐operative administration of a flurbiprofen lozenge reduced the severity, although not the incidence, of early postoperative sore throat . A pre‐operative 2 mg.kg −1 tramadol gargle reduced both the incidence and severity of sore throat for up to 24 h postoperatively in a small study of 50 patients , although 100 mg of intravenous hydrocortisone had no effect .…”
Section: Methodsmentioning
confidence: 95%
“…Smaller tube size [5][6][7] Use of i-gel [50,[63][64][65] SAD rather than tracheal tube [121,122] Video laryngoscopy [9,10] 90°rotational insertion technique, use of introducing stylet for ProSeal LMA laryngeal mask [81][82][83][84][85] Oral rather than nasotracheal intubation [124] Limiting cuff pressure [32][33][34] Cuff pressure limitation ≤ 60 cmH 2 O [88][89][90][91][92][93]96] Cuffed rather than uncuffed tubes [125] Intravenous, topical or inhaled steroids [22][23][24][25] Topical steroids, NSAIDs, tramadol [98,101,102] Limiting tracheal tube cuff pressure [126] Topical NSAIDs [27][28][29]31] Propofol induction and maintenance [106,107] SAD cuff pressure limitation ≤ 60 cmH 2 O [130][131][132][133] Liquorice, magnesium and ketami...…”
Section: Tracheal Intubation Sads Childrenmentioning
confidence: 99%
“…Two clinical studies investigating the effectiveness of flurbiprofen for the prevention of POST were eligible for inclusion in the review (Table 1). 40,41 Uztüre et al 41 evaluated the efficacy of flurbiprofen lozenges for preventing POST, hoarseness and dysphagia symptoms in patients in whom a ProSeal laryngeal mask airway (LMA) was inserted during general anesthesia. A single flurbiprofen lozenge, given 45 min before induction of anesthesia, effectively reduced the severity of early POST (30 min postoperatively) and dysphagia compared with placebo (p<0.05 for both).…”
Section: Post-operative Sore Throat (Post)mentioning
confidence: 99%
“…25,26 It is most commonly used at a dose of 8.75 mg, based on the results of a dose-ranging study that demonstrated linear dose-response relationships for effectiveness and adverse events at doses between 5.0 mg and 12.5 mg. 27 Its use for the symptomatic relief of pharyngitis of viral, bacterial, or unknown etiology has been assessed in a number of studies. 17,22,25,26,[28][29][30][31][32][33][34][35][36][37][38] It has also been evaluated for the relief of postoperative sore throat POST, [39][40][41] a common complication of general anesthesia 42 and tonsillectomy 43 that can negatively impact patients' postoperative comfort.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacologic methods were also used, e.g. NSAID lozenges (flurbiprofen) ( 4 ), lidocaine gel or spray, topical steroid (betamethasone gel on LMA cuff), and intravenous dexamethasone. However, none of them significantly decreased the incidence of POST ( 5 ).…”
Section: Introductionmentioning
confidence: 99%